solve the following system of equations by elimination  2x-6y=3  (1) and 4x+9y=-1  (2)
in Algebra 2 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

1).  2x - 6y = 3

2).  4x + 9y = -1to use elimination we need to get one term to dissappear.  I see that if we multiply the 1) by a -2 this will happen.

(-2) * 1).

-4x + 12y = -6

4x + 9y = -1          add them together.

21y = -7

y = -7/21 = -1/3

plug into 2). to get x.

4x + 9(-1/3) = -1

4x = -1 - 3

4x = -4

x = -1

 

by Level 10 User (55.7k points)

Related questions

1 answer
1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
85,985 questions
91,877 answers
2,227 comments
23,904 users